The Future in the Power Systems Shines With Small Residential Smart Photovoltaic On/Off Cells - Capatina, Octavian; Darie, Silviu (Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
The aging energy infrastructure come to and end. The fossil resources are, politically controlled.The climate change exigencies and his threat to the survival of humanity is real. The increase in domestic electricity consumption have forced the power industry to examine its health.Mankind is at the turning point of its energy future.The rise of renewable technologies can not be ignoring, and its the geographical distribution feature is a huge advantage.A sort of renewables, the photovoltaics, produces everywhere, for everyone.The future power systems will contain intelligent generators, intelligent store facilities and intelligent consumers with intelligent behaviors. Microgrid,a small energy system with locally interconnected generators, consumers and storage facilities, within physical limits,should be parts of large power system. The future does not belong to the microgrid but to the intelligent structure that minimaze the cost and boost the efficiency. Instead of micro, nano or picogrid the Intelligent Energy Cell, IEC, is the answer. IEC besides the today microgrid, contains anintelligent generator (inverter), which optimize the behavior of all component, generator its self, consumer, storage facilities and the exchange with the public grid.This IEC would be in the same time isolated and connected between another IEC’s and the public grid. The future power energy system, the Intelligent Energy System, IES, would be as a tissue of IECs. The next step of development concerns the IES. Here all the major component has its own DNA. In such futurepower systems, all components communicate between them. A superviser task is reduced because every major component, every inelligent energy cell, every consumer would have its proper DNA and in a specific situation know what to do, as the human cells knows. How to cite this article: Capatina O, Darie S. The Future in the Power Systems Shines With Small Residential Smart Photovoltaic On/Off Cells. J Adv Res Alt Energ Env Eco 2018; 5(3): 5-11.